Pharmacogenetic variations and clinical implications of actionable CYP2D6/CYP2C19 variants in Central Indian patients with common mental disorders - Chenchula, Santenna; Shubham, Atal; Abhijit, Rozatkar; Modak, Tamonud; Komal, Kohat; Jhaj, Ratinder; Jitendra, Singh; V., Satyaprakash; Balakrishnan, Sadasivam (Frontiers in Pharmacology, 2025)
IntroductionGenetic polymorphisms in CYP2D6 and CYP2C19 significantly influence the metabolism, efficacy, and safety of antidepressant medications. Limited data exist on the prevalence of these actionable pharmacogenetic variants in the Central Indian population. This study aimed to determine the frequency of clinically actionable Tier-1 alleles, genotypes, and metabolizer phenotypes and to evaluate their clinical relevance in patients with common mental disorders (CMDs).MethodsA total of 509 adults diagnosed with depression and anxiety disorders and receiving SSRI & SNRI antidepressant therapy were enrolled from the Department of Psychiatry, AIIMS Bhopal. Genotyping was performed using the KASP qPCR assay, and CYP2D6 copy number variations (CNVs) were determined using the TaqMan qPCR assay.ResultsAmong the Central Indian cohort, the most frequent CYP2D6 alleles were *10 (21.6%), *41 (17.3%), and *4 (10.4%), while *3 (5.7%), *6 (1.9%). CNVs, Gene deletions(*5) and Gene duplications(xN) were detected in 4.2% and 4.1% of the cohort. For CYP2C19, the *2 (37.3%), *3 (2.3%), and *17 (16.1%) alleles were observed. Non-normal metabolizer phenotypes were present in 46.2% for CYP2D6 and 74.2% for CYP2C19; CYP2D6 ultra-rapid metabolizers accounted for 5.3%. Overall, 86% of participants had at least one clinically actionable pharmacogenetic phenotype. Overall, 7.5% of patients carried CYP2D6 variants and 20.6% carried CYP2C19 variants, for which CPIC guidelines recommend alternative drug selection or dose modification.DiscussionThis study demonstrates a high prevalence of actionable CYP2D6 and CYP2C19 variants in the Central Indian population, underscoring the need for pharmacogenetic integration in psychiatric prescribing in Indian clinical settings, to enhance treatment efficacy and minimize adverse events.